Poly paraphenylene diamine/titanium dioxide/exfoliated graphite nanocomposites: Synthesis and characterisation. (2022) - Rajeshwari, V.; Fernando, Jessica
Abstract: Polymer nanocomposites based on conducting electro active polymers with nanoparticle fillers have attracted considerable attention in recent years because of their highly sought after multifunctional characteristics. In the present study, p-phenylenediamine has been polymerized and composites were prepared by adding TiO2 and exfoliated graphite to the polymer by magnetic stirring. These nanocomposites were characterized by using analytical techniques such as UV–Vis, IR, XRD, AFM, FE-SEM analysis and cyclic voltammetry. Capacitances deduced from CV curves were significant, showing their eligibility for use as capacitors.